Exploring How Female Scientists are Uplifted in Research Networks in STEM Fields in Public Universities in Uganda - Galenda, Safina (East African Journal of Education Studies, 2024)
Participation in research networks is inevitable for the female scientists in the Science Technology Engineering and Mathematics (STEM) fields because they provide a platform for collaborative activities. New research communities of women are created to support each other through mentoring, advancing shared research interests, co-organizing conferences with men, participating in the editorial and the publications. It was on this basis that this study explored how female scientists were uplifted by research networks in STEM fields in public universities in Uganda. This study was anchored on the existential phenomenology by Martin Heidegger in the interpretive world view. Eight female scientists in research networks in STEM fields in public universities in Uganda were interviewed and they were selected from the hard applied and hard pure disciplines as classified in Becher and Biglan’s typology of academic disciplines. Using thematic analysis, two themes such as research collaboration activities and capacity development emerged in this study. This qualitative study set out to explore how female scientists were uplifted in research networks in public universities in Uganda.The public universities included Makerere University, Mbarara University of Science and Technology, Gulu University and Busitema University. Both semi-structured interviews and document check data generation strategies were used in this study. In semi-structured interviews, a sample comprising eight female academics with not less than five years in research networks in public universities were selected, while documents such as the annual reports and strategic plans were used. This study concludes that research networks are uplifting the female scientists in STEM fields in public universities in Uganda because they were internationally exposed, networked, funded, research skills were strengthened, and progressed in career. This study concludes that it was important for female scientists to access physical and human resource in their research networks as this increased their research performance and outputs in STEM fields in public universities in Uganda. This study therefore recommends that, to uplift female scientists in research networks in STEM fields in public universities in Uganda, female scientists in the research networks and senior colleagues should act as ambassadors and mentors to young female scientists in STEM fields